A visible-light-driven Z-scheme heterojunction catalysts via carbon nanodots bridges: Photocatalytic performance and mechanisms investigation. (15th November 2022) - He, Niandan; Yu, Zongxue; Yang, Guangcheng; Li, Xuyang; Xiang, Qingcan; Huang, Qian; Liu, Yucheng
Abstract: In this experiment, a photocatalyst with a Z-scheme heterojunction was constructed that g-C3 N4 nanosheets are connected with NH2 -MIL-88 B(Fe) via carbon quantum dots (CDs) bridges (similar bridge structures) under solvothermal action, where g-C3 N4 nanosheets were prepared by nitric acid pretreatment and secondary thermal oxidation. The composite has higher photo-reduction efficiency of Cr (Ⅵ) and photodegradation efficiency of MB than that of single component. The rate of photocatalytic reduction of Cr (Ⅵ) by the composite material is 21.8 times of g-C3 N4 and 4.1 times of NH2 -MIL-88 B(Fe)/CDs, respectively, and has better chemical stability and reusability. In the whole system, CDs not only acts as a bridge for electron transfer to induce π-π* transition, but also acts as an electron donor and acceptor due to its excellent charge characteristics. It can provide e − for the reduction of Cr (Ⅵ) and consume h +, which can effectively inhibit the recombination of e − /h + and improve the photocatalytic activity and efficiency. The mechanism of Z-Scheme charge transfer was further confirmed by the capture experiment of active species. The activity remains stable and efficient after four catalytic cycles, which offers great possibilities for practical production applications. Graphical abstract: Image 1 Highlights: g-C3 N4 and NH2 -MIL-88 B form heterostructure and CDs forms a bridge at the interface. The composites can effectively photoreduce Cr(Ⅵ) and photodegrade MB. After 90 min of light on, LP-2 can reduce 99% of Cr(Ⅵ) and about 100% of MB. After four cycles, LP-2 has good chemical stability and reusability (90%).